A survey of the knowledge and practices of nursing students of Mbarara University of Science and Technology around Monitoring Fluid Requirements for burns patients on surgical ward at Mbarara Regional Referral Hospital - Joan Atuhaire; Jonathan Kajjimu; Javilla Kakooza Kamya; Grifance Opio; Frank Lubega; Reagan Kakande; William Mwanje; Andrew Tagg (BMC, 2022)
Abstract Background There is a high mortality of burns especially in low- and middle-income countries which already have less developed healthcare systems. Besides, little is known about nursing students' knowledge and practices towards the need to monitor fluid requirements in admitted burns patients. Objective To assess the knowledge and practices of nursing students regarding monitoring fluid requirements for hospitalised paediatrics and adult burn patients on the surgical ward at Mbarara regional referral hospital. Methods We conducted an online descriptive cross-sectional study among clinical nursing students at Mbarara University of Science and Technology (MUST) during September and November 2021. We assessed knowledge and practices using an adapted questionnaire. Summary statistics were then used to describe the data. Results Thirty-seven nursing students (64.9% response rate) participated in our survey. Twenty one (56.8%) were female and had a modal age range of 20-24 years. Nineteen (51.4%) of the students were BNC (Bachelor of Nursing Completion) students, with the rest being BNS (Bachelor of Nursing). More than 75% of students correctly answered each of two out of the ten questions. More than three quarters of the students reported having done each of six out of the eleven practices surveyed. Conclusion Nursing students had poor knowledge and fair satisfactory practices regarding monitoring of the fluid requirements in burns patients. More similar studies are needed to survey more nursing students on this topic and to henceforth evaluate the need for periodic re-trainings and reassessment of clinical skills of nursing students.